Pentingnya Penilaian Pendidikan Karakter Anak Usia Dini - Veny Iswantiningtyas; Widi Wulansari (Proceedings of The ICECRS, 2018)
Kindergarten is an education for early childhood that is on the formal path, Early Childhood education not only to form children who are smart but personable and berakrakter. There are 18 values of character education to be implanted to early childhood. To gauge whether early childhood already has the character applied by the school within a certain period of time, an assessment is required. Assessment of character education is intended to detect the character formed in early childhood during study in Kindergarten.